THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZED LEARNING AND ITS IMPACT ON STUDENT ACHIEVEMENT - Saxanova, L.J.; Allamuratova, N.K.; Raxmetova, L.O. (SCIENCE and SOCIETY, 2023)
This article examines the role of artificial intelligence in personalized learning and its impact on student performance. Artificial intelligence provides an individual educational process by analyzing student data and creating personalized learning trajectories.
Keywords: artificial intelligence; learning; personalized learning; machine learning; data analytics